THE ETHICAL VIOLATIONS ON TELEVISION MEDIA IN THE 2024 GENERAL ELECTION (METRO TV CASE STUDY) - Sidabutar, Franciscus Dicha; Matrano, Victor Rodam; Siahaan, Chontina (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2024)
During the 2024 general election period, there are various types of ethical violations that may occur in news aired by television media. This article discusses ethical violations committed by television media during the 2024 general election period. This research uses qualitative descriptive method with agenda setting theory. This research was conducted by observing several news related to the 2024 general election that has been aired on television media, with case studies from Metro TV. After that, researchers analyze the news to then be able to see the ethical violations that occur. This research resulted in the conclusion that there was an ethical violation in the form of a conglomeration in the news that had been aired by Metro TV. This conglomerate was seen through several YouTube shows owned by Metro TV. This happened because the CEO of Metro TV, namely Surya Paloh, is a top official of the NasDem party who also put his support on Anies-Muhaimin.